Virulence profiles of ten Paracoccidioides brasiliensis isolates obtained from armadillos (Dasypus novemcinctus) - Hebeler-Barbosa, F.; Montenegro, M. R.; Bagagli, E. (Taylor & Francis Ltd, 2003)
Paracoccidioides brasiliensis is the etiologic agent of paracoccidioidomycosis ( PCM), the most important systemic mycosis in Latin America. The armadillo, Dasypus novemcinctus, has been confirmed as the primary natural reservoir of this fungus. Its geographic distribution is similar to that of human PCM. In this study, virulence profiles of 10 P. brasiliensis isolates from different armadillos and of two clinical isolates were tested in an experimental hamster model. Pathogenicity was evaluated by counting cfu and performing histopathological analysis in the testis, liver, spleen and lung. Circulating specific antibodies were measured using enzyme- linked immunosorbent assay ( ELISA). All isolates from armadillos were virulent in the model, with dissemination to many organs. The clinical isolates, which had long been stored in cultured collections, were less virulent. The isolates were classified into four virulence categories according to number of cfu per gram of tissue: very high, high, intermediate and low. This study confirms that armadillos harbor pathogenic genotypes of P. brasiliensis, probably the same ones that infect humans.
Keywords: armadillos; Dasypus novemcinctus; hamster; P. brasiliensis; virulence